Asymmetric flow field-flow fractionation for the monitoring of red wine colloids and macromolecules throughout the winemaking process - Osorio-Macías, Daniel E.; Ferrer-Gallego, Raúl; Choi, Jaeyeong; Bergenståhl, Björn (Frontiers in Soft Matter, 2025)
Colloids and macromolecules are the major compounds in wine particulate matter and play an important role in many wine properties that change during the winemaking process. However, methodologies are lacking to characterize and quantify the changes these compounds undergo throughout the process. This work uses asymmetric flow-field fractionation coupled to multiple detectors (AF4–MALS–dRI–UV) to separate, characterize, and quantify colloidal and macromolecular properties. Furthermore it provides useful information on the evolution and dynamics of these colloidal and macromolecular fractions throughout five winemaking stages. The results showed that the (AF4–MALS–dRI–UV) technique allows monitoring changes in specific colloidal and macromolecular properties during the winemaking process. In this study, three populations were separated and classified according to their nature and main properties throughout the winemaking process. It was observed that concentration, c, and specific absorptivity (ɛ) tend to vary more depending on the wine variety and the vinification stage. However, the maturation and aging stages tended to stabilize changes in the early stages. In contrast, properties such as hydrodynamic radius (rH), molar mass (MW) and regularly the apparent density (p^) tend to remain more stable as the winemaking process progresses. The results demonstrated the use of AF4–MALS–dRI–UV as a robust and feasible technique to separate the wine particle matter and to monitor fundamental colloidal and macromolecular properties in a wide variety of samples without the support of additional techniques throughout the winemaking process.